2022
DOI: 10.1055/s-0042-1758066
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Caries on the Chewing Ability of Children: A Scoping Review

Abstract: Childhood caries might have several effects on the children's general health and growth, including chewing ability. This study aims to identify the evidences found regarding the effect of caries on the chewing ability of children through a scoping review. A scoping review literature search was performed in three databases (Scopus, PUBMED, and Web of Science) without restricting the publicized year. The selected articles were using human as its subjects and aiming to analyze the effects of caries on mastication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Other dental conditions also contribute to changes in the mastication process. Dental caries, whether affecting anterior or posterior teeth, may induce alterations in chewing, which are often reversible with dental treatment of the affected teeth [29]. No studies were found assessing unilateral carious lesions for comparison with the data from this study; however, Nayak et al identi ed a weak association between the presence of caries lesions and PCS [17].…”
Section: Discussionmentioning
confidence: 55%
“…Other dental conditions also contribute to changes in the mastication process. Dental caries, whether affecting anterior or posterior teeth, may induce alterations in chewing, which are often reversible with dental treatment of the affected teeth [29]. No studies were found assessing unilateral carious lesions for comparison with the data from this study; however, Nayak et al identi ed a weak association between the presence of caries lesions and PCS [17].…”
Section: Discussionmentioning
confidence: 55%
“…The teeth are closely spaced above the alveolar bone with adjacent teeth in the oral cavity [32]. They are responsible for grinding and chewing food between the upper and lower jaws [33]. If there is excessive contact between the teeth, the restoration will not fit properly on the abutment teeth in the mouth.…”
Section: Discussionmentioning
confidence: 99%
“…The sappan's leaf and cinnamon's leaf had similarities namely they have hydrophilic components as the major constituents. 25,36 According to, 3 extract that has hydrophilic or polar physical properties, are more effectively inhibits biofilm mass formation of S. mutans, because they can bind the hydrophilic GTF type B which is responsible for bacteria colonization due to its ability to metabolize the core of biofilm mass or Extracellular Polymer Matrix and responsible for bacterial colonization and inhibit the formation of biofilm mass. The sappan's bark 50% not as effective as its leaf, probably because brazilin in sappan's bark is more unstable than flavonoids contained in sappan's leaves and cannot be extracted as perfectly as its leaf.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Untreated cavities can have a negative impact on a person's quality of life by limiting their ability to chew, delaying their ability to grow, and impairing their cognitive abilities. 3 Caries is a process of demineralization or loss of minerals in the hard tissue of the tooth that involves the interaction of several factors, namely the resistance of enamel, microorganisms, carbohydrates, time, and saliva. 4 Acidogenic and aciduric bacteria including Streptococcus mutans (S. mutans) further convert carbohydrate to organic acids, so establishing a low-pH microenvironment in the biofilm.…”
Section: Introductionmentioning
confidence: 99%